2009
DOI: 10.2165/00002512-200926050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and Falls in the Elderly

Abstract: Antidepressants have long been recognized as a contributory factor to falls and many studies show an association between antidepressants and falls. There are extensive data for tricyclic antidepressants (TCAs) and related drugs, and for selective serotonin reuptake inhibitors (SSRIs), but few data for other classes of antidepressants. Sedation, insomnia and impaired sleep, nocturia, impaired postural reflexes and increased reaction times, orthostatic hypotension, cardiac rhythm and conduction disorders, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 77 publications
2
117
2
8
Order By: Relevance
“…These drugs have an alerting effect, impairing sleep duration and quality and causing insomnia, which may result in daytime drowsiness [28]. This can contribute to increase the risk of fall, a well-known contributor to fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs have an alerting effect, impairing sleep duration and quality and causing insomnia, which may result in daytime drowsiness [28]. This can contribute to increase the risk of fall, a well-known contributor to fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Postural hypotension associated with the use of SSRIs is most commonly observed in elderly populations [83]. Paroxetine seems to be the SSRI most frequently associated with orthostatic hypotension at least partly due to its anticholinergic effects [85]. This increased anticholinergic effect may help explain the increased risk of orthostatic hypotension especially in the elderly [86].…”
Section: Cardiovascularmentioning
confidence: 99%
“…There is a large literature on the risk of falls in relation to antidepressant drugs among older people, 148,149 with some studies suggesting that the risk for TCAs is similar to that for SSRIs, 150,151 while others suggest that SSRIs have the highest risk. 152 Few studies have examined effects of individual drugs.…”
Section: Fallsmentioning
confidence: 99%
“…A review of 78 studies 148 found that although there are extensive data for TCAs and SSRIs, there are few data for other antidepressant drugs. The effects of TCAs and SSRIs on the risk of falls were found to be generally similar across studies.…”
Section: Fallsmentioning
confidence: 99%